Adaptation of local lowland rice from West Sumatra on growth, yield, and pest and disease resistance - Salfiati, Salfiati; Putra, Oktaviandra; Ediwirman, Ediwirman (Universitas Muhammadiyah Mataram, 2024)
Rice is a strategic food commodity that needs to be maintained for production stability. This can be done by testing various aspects of both productivity and resistance to pests and diseases. West Sumatra has genetic resources of paddy rice that can be developed into superior varieties. Rice paddy genotypes that have been released into varieties such as Batang Anai, Anak Daro, Bakwan, and Marapulai. But there are also many that have not been made into varieties, including Bujang Marantau, Kuriak Kusuik, Kuriak Putiah, which are still cultivated by farmers. Therefore, testing the adaptability of local paddy rice genotypes is one of the initial strategies. The experiment was conducted on paddy fields in 2 (two) locations, Tolatang Kamang and Ampek Angkek Agam Regency, West Sumatra Province. The experiment was conducted from February to June 2022. The experiment used a Randomised Block Design with 3 blocks. Treatments consisted of 5 (five) phenotypes including; Kusuik Putiah, Kuriak Kusuik, Kuriak Putiah, Ampek Bulan Putiah, and Cantik Manis. Variables observed in the field during plant growth from the vegetative, generative phase to harvest include; plant height, number of productive tillers per clump, panicle length, flowering age, number of grains per panicle, number of full grains per panicle, harvest age, weight of 1,000 grains, dry grain weight per ha, resistance to brown stem leafhopper, and bacterial leaf blight. Observational data were analyzed statistically using the STATISTIX ver 8.0 program. Brown planthopper pest attack was observed by referring to the criteria set by IRRI. The results of the study can be concluded, Kusuik Putih is one of the local paddy rice genotypes from West Sumatra that can be proposed as a candidate for new superior varieties with dry grain weight reaching 6.95 t per ha, but, bacterial leaf blight resistance is still classified as susceptible to moderately vulnerable, followed by other local rice such as Kuriak Putiah (5.92 t.ha 1), Cantik Manis (5.55 t.ha 1), Ampek Bulan Putiah (5.30 t.ha 1), and Kuriak Kusuik (4.95 t.ha 1), which are moderately resistant to brown stem leafhopper and bacterial leaf blight.